STRATEGI PEMBELAJARAN AKTIF UNTUK ANAK USIA DINI - Uswatun Hasanah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: The role of teachers basically directs children as excellent generation, because the potential of children will not grow by itself without the help of teachers. Children need an environment that enables their potential to grow optimally. Children have their own unique world with children's point of view. Almost all of its activities are playing, exploring the objects that are around them is a fun activity. Thus, to face them requires active learning. The types of integrated active strategies for early childhood, namely: (1) BCCT strategy or (Beyond Center and Circle Time); (2) Throwing Ball Strategy; (3) Simple Brainstorming Strategy; (4) Drill strategy of Active Stories; (5) Record tracking strategy; (6) Problem-based learning. Keywords: strategi, pembelajaran aktif, anak usia dini.